Acclimated methanotrophic consortia for aerobic co-metabolism of trichloroethene with methane. (August 2019) - Wang, Chun-Chin; Li, Chen-Huei; Yang, Chu-Fang
Abstract: Trichloroethene (TCE) is extensively used as metal degreaser and causes a serious impact on the soil and groundwater environment due to improper disposal and control. Aerobic co-metabolism strategy relying on methane-oxidizing bacteria is quite attractive to bioremediate TCE contaminated site because no toxic intermediates are produced. Methane monooxygenase (MMO) produced by these methanotrophs can transform TCE into unstable TCE epoxides to accelerate the TCE removal rate. To investigate the potential of applying TCE aerobic co-metabolism strategy in Taiwan, methanotrophic consortia from chloroethenes contaminated groundwater were enriched in this study. Their bacterial communities and MMO genes were analyzed. The selected enriched methanotrophic consortia were then used to evaluate the feasibility of TCE aerobic co-metabolism in batch experiments. The bacterial community diversities significantly declined and methane-oxidizing bacteria became dominant after acclimation. Methane was consumed by all methanotrophic consortia during acclimation and, at the same time, the functional genes mxaF, mmoX and pmoA were successfully amplified from all consortia, except for gene mmoX of consortium C, after enrichment. The TCE removal efficiencies of consortium A were between 69.6 and 90.4% which was superior to those of consortium C (64.3–75.1%). It is possible to apply the aerobic co-metabolism strategy to bioremediate TCE contaminated sites in Taiwan. Highlights: Methanotrophs became dominant after methane domestication. The functional genes mxaF, mmoX and pmoA could be successfully amplified from the enriched methanotrophic consortia. The TCE removal efficiency of consortium A was superior to that of consortium C. It is possible to apply aerobic cometabolism strategy to bioremediate TCE contaminated sites.